The secret lives of booksellers and librarians : true stories of the magic of reading - Patterson, James; Eversmann, Matt; Mooney, Chris (Century, 2024)
In this love letter to the heroes of literacy, James Patterson uncovers true stories from booksellers and librarians. Prepare to enter a world where you can feed your curiosities, discover new voices, and find whatever you need. Meet the smart and talented people who live between the shelves - and who can't wait to help you find your next great read.
Keywords: lukeminen; kirjakauppiaat; kirjastonhoitajat; kirja-ala; kirjastoala; henkilöhistoria